2013
DOI: 10.1627/jpi.56.69
|View full text |Cite
|
Sign up to set email alerts
|

グリーン有機分子変換プロセスを指向したセリア担持ルテニウム触媒の開発

Abstract: Solid Ru/CeO2 catalysts, which are effective for the catalysis of various highly atom-efficient organic transformations such as dehydrogenative synthesis of indole, regio-and stereo-selective coupling of unsaturated hydrocarbons, C _ C bond-forming reactions via the activation of aromatic C _ H bonds, and selective addition of carboxylic acids to alkynes, have been developed. For these reactions, CeO2-supported and, in some cases, ZrO2-supported catalysts show excellent activities, whereas ruthenium catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…On the other hand, considerable attention has recently focused on the use of supported metal catalysts for organic transformations from the viewpoint of green chemistry due to the ease of separation from the reaction mixture and recycling of the catalyst. In the course of our study on the development of supported Ru catalysts that are effective for organic synthesis, we demonstrated that phosphine-modified Ru/CeO 2 catalysts efficiently promoted various kinds of C–C bond-forming reactions involving C–H bond activation. Fortunately, we found that Ru/CeO 2 catalysts modified with 3 equiv of PCy 3 to Ru (3PCy 3 -Ru/CeO 2 ) promoted the coupling reaction of 1a with 2a to give 3aa in a good yield (Scheme ). Notably, the supported Ru catalyst required no external base for the reaction to proceed thanks to the basic surface of CeO 2 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, considerable attention has recently focused on the use of supported metal catalysts for organic transformations from the viewpoint of green chemistry due to the ease of separation from the reaction mixture and recycling of the catalyst. In the course of our study on the development of supported Ru catalysts that are effective for organic synthesis, we demonstrated that phosphine-modified Ru/CeO 2 catalysts efficiently promoted various kinds of C–C bond-forming reactions involving C–H bond activation. Fortunately, we found that Ru/CeO 2 catalysts modified with 3 equiv of PCy 3 to Ru (3PCy 3 -Ru/CeO 2 ) promoted the coupling reaction of 1a with 2a to give 3aa in a good yield (Scheme ). Notably, the supported Ru catalyst required no external base for the reaction to proceed thanks to the basic surface of CeO 2 .…”
Section: Resultsmentioning
confidence: 88%
“…Supported Ru catalysts were prepared through the method reported in our previous literature. A 1.0 g amount of a support was added to a solution of [RuCl 2 ( p -cymene)] 2 (0.20 mmol) in 10 mL of methanol in air at 50 °C After impregnation, the resulting powder was calcined in air for 30 min to afford the Ru­(2.0 wt %)/CeO 2 catalyst. The modification of Ru/CeO 2 catalyst by 3 equiv of PCy 3 to Ru was performed as follows: 250 mg (0.050 mmol as Ru) of Ru/CeO 2 and PCy 3 (0.15 mmol) was heated at 100 °C for 20 min under hydrogen atmosphere (1 atm) without any solvent.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…This result indicates that Ru(IV)=O species functioned as a precursor of the active species for the C _ C bond-forming reaction 14),15) . Ru/CeO2 and Ru/ZrO2 catalysts showed high activity for C _ C bond-forming reactions 16) via C _ H bond activation, such as aromatic C _ H arylation 17) , alkylation 18) and alkenylation 19) . The appropriate choice of support enabled to control precise structure of Ru species on their surface, thereby allowed highly dispersed Ru(IV)=O species function as a catalyst precursor for C _ C bond-forming reactions via the activation of inactive C _ H bonds 20),21) .…”
Section: Addition Of C-h Bond To Alkynesmentioning
confidence: 99%
“…Codimerization of alkenes is a promising, atom-efficient synthetic method that affords highly substituted alkenes with various functionalities from simple alkenes. Thus far, Co, Ni, ,, Ru, Rh, ,,, Pd, other transition-metal complexes, and Lewis or Brønsted acids have been used as catalysts for this r...…”
Section: Introductionmentioning
confidence: 99%